2013
DOI: 10.1002/acr.22073
|View full text |Cite
|
Sign up to set email alerts
|

“Somebody to Say ‘Come On We Can Sort This’”: A Qualitative Study of Primary Care Consultation Among Older Adults With Symptomatic Foot Osteoarthritis

Abstract: ObjectiveTo examine the experiences of primary care consultation among older adults with symptomatic foot osteoarthritis (OA).MethodsEleven participants (6 women and 5 men) ages 56–80 years who had radiographically confirmed symptomatic foot OA and consulted a general practitioner in the last 12 months for foot pain were purposively sampled. Semistructured interviews explored the nature of the foot problem, help-seeking behaviors, and consultation experiences. Verbatim transcripts were analyzed using interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 15 publications
5
33
0
Order By: Relevance
“…We can postulate that women from the general population may be willing to persevere with fashionable but ill‐fitting footwear that may be causing some mild foot pain, whereas women who have disease‐related foot pain and/or deformities may be less resilient or less willing to persist with such footwear due to the potential for increased levels of foot pain and discomfort. These findings are reflective of past studies of people with RA and OA, suggesting that body image is an important factor in relation to perceptions of appropriate footwear . In contrast, a recent study of footwear choices in a predominantly male cohort with gout found that footwear choices were driven more by comfort, fit, and support .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We can postulate that women from the general population may be willing to persevere with fashionable but ill‐fitting footwear that may be causing some mild foot pain, whereas women who have disease‐related foot pain and/or deformities may be less resilient or less willing to persist with such footwear due to the potential for increased levels of foot pain and discomfort. These findings are reflective of past studies of people with RA and OA, suggesting that body image is an important factor in relation to perceptions of appropriate footwear . In contrast, a recent study of footwear choices in a predominantly male cohort with gout found that footwear choices were driven more by comfort, fit, and support .…”
Section: Discussionsupporting
confidence: 68%
“…A qualitative study of symptomatic foot OA has recently highlighted the importance of suitable footwear for female OA patients . In particular, women expressed that footwear and personal appearance were important elements of desirable self‐image, arguably similar to previous findings from studies of women with RA .…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Egerton et al () (Egerton et al, ) and many others have reported the perception that ‘OA is not that serious’ and that ‘personal beliefs are at odds with providing recommended practice’. A body of literature suggests that OA is a low priority to both HCPs and patients, and, that HCPs' personal beliefs do not always align with recommended guidelines (Egerton et al, , Paskins, Sanders, & Hassell, , Paskins, Sanders, & Hassell, , Thomas, Moore, Roddy, & Peat, , Jinks, Ong, & Richardson, ). In addition, findings illustrated how self‐management was not viewed as core business by some GPs and because the condition didn't align to pay‐for‐performance targets, and implementation was reported not to provide any benefits to the practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although reluctant to seek medical advice the older people wanted support and information on which to base their decisions on how to manage the pain. Older people are often reluctant to present a fragile or ageing self to others (Thomas, Moore, Roddy, & Peat, ) so nurses need to provide support that challenges this stereotype and promotes optimal functioning to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%